Researching with families : ethical issues and situations - Dockett, Sue; Perry, Bob; Kearney, Emma; Hampshire, Anne; Mason, Jan; Schmied, Virginia (Contemporary issues in early childhood, 2009)
This article draws on an Australian project engaging with families with complex support needs as their children start school. The project itself is focused on developing collaborative research relationships between families, community support agencies and researchers with the aim of investigating what happens for families during the transition to school. In particular, the project has focused on developing strategies that promote recognition of family strengths, as well as challenges, and that support a positive start to school education. This article reports a range of ethical issues and situations encountered throughout the project. The aim of reporting these is to share some of the critical reflections about the assumptions underpinning the research, ethical engagement with research participants, and the responsibilities researchers have. In particular, the authors share reflections about the nature and implications of conducting research with families, accessing research participants and strategies for engaging with research participants. The approach taken in the project, and this article, reflects assumptions about research as an ethical process and the need for researchers to consider the ethical issues and situations they meet within research contexts. [Author abstract]